2018
DOI: 10.1038/s41598-017-18261-6
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and training-induced cortical plasticity in MD patients: Hints from lateral masking

Abstract: Macular degeneration (MD) affects central vision and represents the leading cause of visual diseases in elderly population worldwide. As a consequence of central vision loss, MD patients develop a preferred retinal locus (PRL), an eccentric fixation point that replaces the fovea. Here, our aim was to determine whether and to what extent spontaneous plasticity takes place in the cortical regions formerly responding to central vision and whether a visual training based on perceptual learning (PL) can boost this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 47 publications
4
28
0
1
Order By: Relevance
“…It should be noted that our training protocol is different from typical perceptual learning studies. Previous psychophysical studies have shown that training enhances the ability to identify or detect the target in the midst of flankers (Sun et al, 2010;Hussain et al, 2012;Mayhew et al, 2012;Zhu et al, 2016;Maniglia et al, 2018). In these studies, the same task was used in both the training and test phases, and the learning effect was often specific to features of the trained stimulus.…”
Section: Orymentioning
confidence: 99%
“…It should be noted that our training protocol is different from typical perceptual learning studies. Previous psychophysical studies have shown that training enhances the ability to identify or detect the target in the midst of flankers (Sun et al, 2010;Hussain et al, 2012;Mayhew et al, 2012;Zhu et al, 2016;Maniglia et al, 2018). In these studies, the same task was used in both the training and test phases, and the learning effect was often specific to features of the trained stimulus.…”
Section: Orymentioning
confidence: 99%
“…Previous studies have observed that collinear lateral inhibition can be reduced using perceptual learning in observers with normal vision 12 and observers with macular degeneration 10 . Maniglia et al 12 reported an approximately 40% reduction of peripheral collinear lateral inhibition after training in healthy observers.…”
Section: Discussionmentioning
confidence: 96%
“…In this case, with the low contrast target, we would have obtained increased contrast enhancement at the range of target-to-flanker distances at which facilitation occurs in normal vision. In the previous literature, the reduced collinear inhibition found in MD has been interpreted as a sign of neural plasticity, linked with a change in receptive field size 35,49 . We shed new light on this phenomenon and propose a different interpretation.…”
Section: Discussionmentioning
confidence: 96%
“…Since lateral connectivity has been shown to increase with practice in normal 31,34,45 and pathological vision 46–48 , use-dependent cortical reorganization might change the observed contextual influences. A partial support for the cortical reorganization hypothesis comes from recent papers showing that MD patients exhibited a modulation of contextual influences in respect of controls 35,49 . In the present study, we further address this issue attempting to specify the underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%